2016
DOI: 10.15835/nbha44110257
|View full text |Cite
|
Sign up to set email alerts
|

Water Supply and Temperature Effects on Some Nutritive Constituents of Direct Sown Onion

Abstract: Irrigation is a prerequisite for economical onion production under dry conditions. However, its effect on dry matter and nutrient content often remains a concern for growers. A direct sown onion hybrid was grown under open field, rain-fed and irrigated conditions for three years, investigating the effects of air temperature and water supply on some nutritive constituents. Dry matter, storage sugar, total flavonol and total polyphenol content showed strong positive correlation with average air temperature and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The year 2016 recorded the highest amount of precipitation during growing season (63.47 mm). According to Ombodi et al [28], fibre and ash content were found to be the most stable nutritional characteristics of onions, affected neither by the environmental conditions nor by the irrigation. The cultivar Rote Laaer showed a higher content of crude fibre in all years in comparison to the cultivar Stuttgarter Riesen.…”
Section: Discussionmentioning
confidence: 99%
“…The year 2016 recorded the highest amount of precipitation during growing season (63.47 mm). According to Ombodi et al [28], fibre and ash content were found to be the most stable nutritional characteristics of onions, affected neither by the environmental conditions nor by the irrigation. The cultivar Rote Laaer showed a higher content of crude fibre in all years in comparison to the cultivar Stuttgarter Riesen.…”
Section: Discussionmentioning
confidence: 99%